Postextraction Alveolar Ridge Preservation: Biological Basis and Treatments - Giorgio Pagni; Gaia Pellegrini; William V. Giannobile; Giulio Rasperini (Hindawi Limited, 2012)
Following tooth extraction, the alveolar ridge undergoes an inevitable remodeling process that influences implant therapy of the edentulous area. Socket grafting is a commonly adopted therapy for the preservation of alveolar bone structures in combination or not with immediate implant placement although the biological bases lying behind this treatment modality are not fully understood and often misinterpreted. This review is intended to clarify the literature support to socket grafting in order to provide practitioners with valid tools to make a conscious decision of when and why to recommend this therapy.